PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI SEKOLAH TINGGI PARIWISATA BALI INTERNASIONAL - Ni Komang Nariani (Institut Pariwisata dan Bisnis Internasional, 2016)
The International Bali Tourism Institute is one of Private School in Tourism and Hospitality.. High quality human resources are urgently needed by an institution to be able to compete and develop its potential as an embodiment of the performance. Efforts to improve organizational performance should be started from the employee's performance. Many factors affect the performance of the employee. This research focuses the employee performance on three things: compensation, leadership and work environment.The study uses 74 respondents, employees of The International Bali Tourism Institute. The research aimed to determine the effect of compensation, leadership and work environment to employee’s performance at the College of Tourism Bali International. The data analysis is using multiple linear regression. The results showed there are significant positive and significant between compensation and leadership on employee performance, meaning that if the compensation and leadership increases, the performance of employees will increase. There is a positive effect but not significant between the work environments on employee performance, meaning that although the work environment increases employee performance has not increased. There is a positive and significant influence between compensation, leadership and work environment simultaneously on employee performance, meaning that if the compensation, leadership and work environment increases, the performance of employees will increase.